Hubungan kadar Pb dalam darah dengan prestasi belajar pada anak sekolah di SDN Grinting 01 Kecamatan Bulakamba Kabupaten Brebes - Romli, M; Suhartono, Suhartono; Setiani, Onny (Jurnal Kesehatan Lingkungan Indonesia, 2016)
Title : Association between Blood Lead Level and Learning Achievement on the Students at Grinting 01 Elementary School, Bulakamba District, Brebes RegencyBackground: Plumbum (Pb) is a highly poisonous heavy metal, especially for the children. Pb enters the human body through the respiratory and gastrointestinal tract, and also skin. The aim of this study was to determine the correlation between blood lead level and the learning achievement on the students in Grinting 01 Elementary School, Bulakamba District, Brebes Regency. Methods: This study was an observational research using cross sectional design.  The subjects were 51 students. The data were collected using interview and observational field. The exposure of blood lead level was measured by detecting Pb content in blood according to the result of laboratory test by ASS method (Atomic absorbance spectrometer), and the learning achievement was measured using MST (Middle Semester Test) score of the students. Univariate analysis and bivariate analysis (Chi-Square) were used to analyze the data. Results: The result of bivariate test indicated that there was no correlation between blood lead level and learning achievement with p >0.05. For in the ehole samples, the blood lead level were more than Normal standard of CDC (≥5 µg/dL) with the highest Pb in blood is 48.39 µg/dL and the lowest is 11.06 µg/dL. Conclusion: In conclusion, Pb concentration - in blood on the children does not influence the learning achievement directly.